Waste heat recovery from a gas turbine: Organic rankine cycle - Meor Said, M.A. (Springer Verlag, 2019)
This chapter presents a study on optimization and parametrization of thermodynamic modelling of Organic Rankine Cycle (ORC) for waste heat recovery (WHR) of a gas turbine engine. The major aim of the study is to present a feasibility analysis in terms of thermodynamic performance for an integrated waste heat recovery system with a gas turbine system. The sections in this chapter provide detail out the findings at the preliminary stages. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2019.